2011
DOI: 10.1097/mcg.0b013e318207f76c
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic Understanding of Probiotic Effects in Humans With Irritable Bowel Syndrome

Abstract: This metabonomic study suggests that in a subset of IBS patients there exists a potential dysregulation in energy homeostasis (serum glucose) and liver function (serum tyrosine) that may be improved through probiotics supplementation. Moreover, global metabolic profiling highlights the potential of metabonomic approach for assessing bowel diseases or symptoms with respect to host metabolic perturbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 0 publications
0
58
0
1
Order By: Relevance
“…Significant pain alleviation was not found in 16 studies (6,19,20,(22)(23)(24)(25)(26)29,32,34,(36)(37)(38)(39), although a pain alleviation trend was found in 4 studies (5,23,32,37). Both the TG and Studies identified from bibliographic databases n = 252…”
Section: Abdominal Pain or Discomfortmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant pain alleviation was not found in 16 studies (6,19,20,(22)(23)(24)(25)(26)29,32,34,(36)(37)(38)(39), although a pain alleviation trend was found in 4 studies (5,23,32,37). Both the TG and Studies identified from bibliographic databases n = 252…”
Section: Abdominal Pain or Discomfortmentioning
confidence: 99%
“…Eighteen studies evaluated the effects of probiotics on distension (4,5,(19)(20)(21)(22)(23)(24)(25)27,(29)(30)(31)(34)(35)(36)(37)39 (19,20,25,29,31,34,36,39).…”
Section: Abdominal Bloating or Distensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Немногие нежела-тельные явления были зарегистрированы в обеих груп-пах пробиотиков и плацебо [83]. Те же результаты были достигнуты с помощью обширного обзора других 9 иссле-дований, в которые, в соответствии с критериями «Рим II» или «Рим III», были включены 324 пациента с различны-ми типами СРК [84,85].…”
unclassified
“…1 H NMR spectroscopy can be available detailed information on the concentration of the low-molecular weight metabolites in body fluids such as serum, plasma and urine in a single experiment [3,4,5].…”
Section: Introductionmentioning
confidence: 99%